2020
DOI: 10.1007/978-3-030-45778-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Hierarchical Deep Learning Approach for Intrusion Detection

Abstract: Nowadays, it is almost impossible to imagine our daily life without Internet. This strong dependence requires an effective and rigorous consideration of all the risks related to computer attacks. However traditional methods of protection are not always effective, and usually very expensive in treatment resources. That is why this paper presents a new hierarchical method based on deep learning algorithms to deal with intrusion detection. This method has proven to be very effective across traditional implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A bi-level hierarchical classification methodology using ML has been proposed in [13] to identify the different types of secondary tasks drivers are engaged in using their driving behavior parameters. The authors in [14] indicated that splitting the classification task into sub-classification tasks can improve the accuracy rate on some non-BGP benchmark cyberattack datasets. Currently, ML-based self-maintenance solutions for SICNs are not available.…”
Section: A Employing ML Methodsmentioning
confidence: 99%
“…A bi-level hierarchical classification methodology using ML has been proposed in [13] to identify the different types of secondary tasks drivers are engaged in using their driving behavior parameters. The authors in [14] indicated that splitting the classification task into sub-classification tasks can improve the accuracy rate on some non-BGP benchmark cyberattack datasets. Currently, ML-based self-maintenance solutions for SICNs are not available.…”
Section: A Employing ML Methodsmentioning
confidence: 99%
“…Through training, this model effectively differentiated complex attacks and accurately analyzed unknown web-based attacks.F. Alin et al [36] proposed a hierarchical deep learning approach for intrusion detection. Henry et al [37] The author proposes a technique that combines CNN and GRU, in which different CNN-GRU combination sequences are proposed to optimize network parameters.…”
Section: Intrusion Detection Modelmentioning
confidence: 99%
“…In the CICIDS2017 dataset, there are 15 classes including the benign class and among the recent machine-learning based solutions evaluated on this dataset, the number of classes has at least eight different values. In [16,21,22,28], all 15 classes are used as the classifier outputs.…”
Section: Classifier Outputmentioning
confidence: 99%